2021
DOI: 10.51414/sei2021.026
|View full text |Cite
|
Sign up to set email alerts
|

SDG localization baseline: How local-level actors are driving change and advancing the achievement of the 2030 Agenda

Abstract: Localization of the Sustainable Development Goals (SDGs) refers to the process of defining, implementing, and monitoring strategies at the local level to achieve global, national, and subnational sustainable development goals and targets. The key question addressed by this baseline document is how SDG localization can be practically, efficiently, and effectively implemented in what remains of the Decade of Action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Assessments have mainly been based on national SDG review reports such as the Voluntary National Reviews (VNRs). Recently, [11] found that a key barrier to effec-tive localization is often found in weak institutions and systems of governance. In many cases, the coordination of SDG implementation is led mainly by the national government due to low engagement and participation of local governments.…”
Section: What Is Sdg Localization?mentioning
confidence: 99%
“…Assessments have mainly been based on national SDG review reports such as the Voluntary National Reviews (VNRs). Recently, [11] found that a key barrier to effec-tive localization is often found in weak institutions and systems of governance. In many cases, the coordination of SDG implementation is led mainly by the national government due to low engagement and participation of local governments.…”
Section: What Is Sdg Localization?mentioning
confidence: 99%